In vitro maturation of buffalo oocytes and fertilization by cattle spermatozoa (Bangladesh Journal of Animal Science, 2012)
The present research was undertaken to explore the maturation of buffalo oocytes using bovine follicular fluid (BFF) and bovine serum albumin (BSA), as well as subsequent fertilization using cattle spermatozoa. The cumulus oocyte complexes (COCs) were collected by aspiration of slaughterhouse buffalo ovaries. Maturation was performed in TCM 199 supplemented with 10% BFF, 5% BSA or without supplementation (control). The COCs were fertilized in Brackett and Oliphant (BO) medium using capacitated fresh cattle spermatozoa. It was observed that the percentage of COCs reached to M-II stages were 40.78±3.84, 65.74±2.39 and 67.52±0.85; normal fertilization (formation of 2 pronuclei) were 23.28±3.00, 29.30±0.73 and 30.52±1.21 for control, 10% BFF and 5% BSA supplementation, respectively. The supplementation of BFF (10%) and BSA (5%) were given similar results on maturation and increased significantly (p